Quantifying the Impact of Renewable Energy Futures on Cooling Water Use1. (28th April 2014) - Baker, Jonathan; Strzepek, Kenneth; Farmer, William; Schlosser, C. Adam
Abstract This article presents an empirically based model, WiCTS (Withdrawal and Consumption for Thermoelectric Systems), to estimate regional water withdrawals and consumption implied by any electricity generation portfolio. WiTCS uses water use rates, developed at the substate level, to predict water use by scaling the rates with predicted energy generation. The capability of WiCTS is demonstrated by assessing the impact of renewable electricity generation scenarios on water use in the United States (U.S.) through 2050. The energy generation scenarios are taken from the Renewable Energy Futures Study performed by the U.S. National Renewable Energy Laboratory of the U.S. Department of Energy. Results indicate reductions in water use are achieved under these renewable energy scenarios. The analysis further explores the impact of two modifications to the modeling framework. The first modification presumes geothermal and concentrated solar power generation technologies employ water‐intensive cooling systems vs. cooling technology that requires no water. The second modification presumes all water‐intensive cooling technologies use closed cycle cooling (as opposed to once‐through cooling) technologies by 2050. Results based on one of the renewable generation scenarios indicate water use increases by over 20% under the first modification, and water consumption increases by approximately 40% while water withdrawals decrease by over 85% under the second modification.